Orientação informacional da Rede de Bibliotecas da Fiocruz - Segemar Oliveira Magalhães (2017)
The present research is descriptive of a quantitative and exploratory nature with a view to collect data that evidences the Informational Orientation of the Fiocruz Libraries Network through the perceptions of the Managers and Officers regarding the practices of information technology, information management practices and behaviors / Values related to information with a view to organizational performance. The concept of Information Orientation (OI) can be measured by means of a diagnostic tool to evaluate organizational practices related to the use of information technology, information management and behaviors / Values related to information. Among the competencies of the Oswaldo Cruz Foundation (FIOCRUZ), the institution has the State duty to carry out activities of production, capture and storage, analysis and dissemination of information for health, science and technology. The Fiocruz Libraries Network has State responsibilities regarding the technical processing, management and dissemination of information on health, science, technology and innovation, in order to promote citizenship and decision-making. The research was carried out through an online questionnaire, with questions about Information Orientation that reflect the theoretical reference and the research problem, adapted from an instrument used in the "Informational Orientation in higher education institutions of Belo Horizonte" and partially used "Behaviors and values related to information in an airline company". The Term of Free and Informed Consent presented the research with benefits and risks, as well as ensuring secrecy and anonymity. The research tool in the form of an online questionnaire was applied to the managers and employees of the Fiocruz Libraries Network, in Feb./17 to 80 people, with the participation of 32 respondents. Information Technology Practices of the Fiocruz Libraries Network, for technical processing, performance, efficiency, integration, connections, products & services, creativity, sharing and trends have prevalence in the assertive "agree" and "totally agree" with the 32 Respondents of the research. Information Management Practices of the Fiocruz Libraries Network, for searching information, internal sources, external sources, qualification, classification, indexing, integration, training, decision making, information gathering and updating of databases Of data have the "agree" and "totally agree" assertions by the 32 respondents. Behaviors and values related to information from the Fiocruz Libraries Network, to stimulate the constant search for information, use of information, improve products & services and / or network processes, promote a climate of trust, sharing, decision making , collective interest, avoidance of individualism, secrecy and performance, there were higher frequencies in the "agree" and "totally agree" assertions of the 32 respondents. It is concluded that there is Informational Guidance of the Fiocruz Libraries Network, through a survey conducted with managers and employees. Working Groups - WGs on "Aleph - Implementation of the Collection Management System", "Physical and Web Accessibility" and "Development of Collections, Users' Study and collection digitization policies" are being developed in the Fiocruz Library Network . Further research on Library Network Information Orientation is needed to describe information technology practices, information management practices, and behavior / values related to information with a view to organizational performance.